Analisis Dampak Lalu Lintas Pasar Ngablak Kabupaten Magelang: Traffic Impact Analysis Of Ngablak Market Magelang County - Yulianyahya, Raafi Widyaputra; Kasikoen, Ken Martina (Media Ilmiah Teknik Sipil, 2024)
Changes in the structure of urban space will affect movement patterns, ultimately burdening the existing road network in an area. Traffic Impact Analysis (TIA) is an analysis of the influence of land-use development on the system of traffic flow movement around the development; this is caused by the emergence of new traffic, shifting traffic, and vehicles coming in and out of or to the development land. The construction of Pasar Ngablak can have a new traffic impact and increase the traffic load around the market, disrupting traffic links that can reduce the level of road services. This study aims to analyze the impact of market development activities that are useful to minimize traffic impact and provide appropriate recommendations. The research method used was the approach of the 1997 Indonesian Road Capacity Manual (MKJI, 1997), with the results of the delay value and degree of saturation. The results of the delay value and degree of saturation are used to see the existing conditions and during operation. However, predictions for the next 5 (five) years after development need to be watched out for and given appropriate recommendations because there is an increase in traffic movement around the market